(untitled) (Global Journal of Science Frontier Research, 2023)
Deforestation and forest degradation are related to human-induced activities practiced in comparison to the conservation of forest and its management in Nigeria This work evaluated the diversity status of tree species in Shasha Forest Reserve utilizing a simple random sampling method for plot demarcation with a transect established in the assessment area Sixteen sample plots of 25 m x 25 m were established within the minimally protected and unprotected plots of the reserve Descriptive statistics were used to analyze the data generated The results of the tree appraisal showed that 644 individual trees and 60 different tree species 23 families were identified